INTEGRATING TRADITIONAL TIB-E-NABAVI WITH CONTEMPORARY MEDICATIONS FOR EFFECTIVE CONGESTIVE HEART FAILURE MANAGEMENT (The Research of Medical Science Review, 2025)
The present study aimed to discuss treatment of congestive heart failure (CHF) by Tib-e-Nabavi in comparison to modern medicine. CHF is a complex clinical disorder the incidence of which increases with age. The main causes of CHF are coronary artery disease [CAD], ischemic heart disease [IHD], myocardial infarction [MI], hypertension [HTN] and pressure or volume overload. It is diagnosed by electrocardiography [ECG], Echocardiography, BNP level and other lab tests. In Tib-e-Nabavi it is treated with milk, barley, honey and dates and its importance is discussed with reference to Holy Quran and Ahadith. Description according to modern science and benefits in CHF are also given. The other plants that are used for the treatment include the Saussaurea lappa, Cichorium intybus and Nigella sativum. In the modern medicine it is treated by the diuretics, vasodilatory agents and inotropic drugs. The data collected by reviewing medical books, medicinal books, Holy Quran, Islamic literature, journals, research articles and organized in a systemic way. Finally, it is concluded that treatment of CHF by modern medicines in combination with Tib-e-Nabavi is beneficial for the patient and increase the compliance rate of patient.